2008
DOI: 10.3155/1047-3289.58.5.684
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Diurnal Variability in Airborne Mold from an Indoor Residential Environment in Northern New York

Abstract: It is well known that characterization of airborne bioaerosols in indoor environments is a challenge because of inherent irregularity in concentrations, which are influenced by many environmental factors. The primary aim of this study was to quantify the day-to-day variability of airborne fungal levels in a single residential environment over multiple seasons. Indoor air quality practitioners must recognize the inherent variability in airborne bioaerosol measurements during data analysis of mold investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
6
12
0
Order By: Relevance
“…However, the gravimetric PM 5 measurements were very well correlated with the OPC measurements for the hospital hallway (R 2 ≥ 0.89 for all OPC sizes). The lack of a consistent correlation between Aspergillus and PM is consistent with the findings of LeBouf et al (2008). In that study, no correlation was observed between culturebased measurements of fungal levels inside residences and indoor PM 2.5 (and PM 10 ) measurements.…”
Section: Aspergillus Compared With Pmsupporting
confidence: 88%
“…However, the gravimetric PM 5 measurements were very well correlated with the OPC measurements for the hospital hallway (R 2 ≥ 0.89 for all OPC sizes). The lack of a consistent correlation between Aspergillus and PM is consistent with the findings of LeBouf et al (2008). In that study, no correlation was observed between culturebased measurements of fungal levels inside residences and indoor PM 2.5 (and PM 10 ) measurements.…”
Section: Aspergillus Compared With Pmsupporting
confidence: 88%
“…This same phenomenon was alluded to previously by other researchers (LeBouf, et al 2008). In this study that pattern held true for months March through November, but when the December through February data was analyzed a new pattern arises.…”
Section: Resultssupporting
confidence: 54%
“…Diurnal variations of mold counts were not significant, probably due to the relatively lower RH levels observed in this study. Interday variability of mold count for both seasons was found to be associated with rapidly growing mold sources and varying environmental conditions (LeBouf et al, 2008). Diurnal variations of both bacteria and fungi were found for morning and afternoon periods of a day in university rooms, and both bacterial and fungal levels were found to be lower in the morning than in the afternoon (Stryjakowska-Sekulska et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…However, levels and compositions of bioaerosols can be affected by the sampling time, sampling day, and season. Nevertheless, only a few research pointed out the importance of diurnal and/or daily variations of bioaerosols (Law et al, 2001;LeBouf et al, 2008;Stryjakowska-Sekulska et al, 2007;Zhu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%